(3OGeZ GdHGWd hMJa GdefGVds - (3Ydj Hf eMeO Hf GdhdjO GdGfa,J (B612 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eXgQ Ojf GdMb Ydi GdOjf cdg hdh cQg GdeTQchf s
(3BNQgG (B:s
(3hEUOGQ MGUd Ydi GdXf GdeHfi Ydi TaG LQa gGQ , eYJQa HGdNWC GdehQO dCgdg YGde jJhHhG Yfg Edi bYQ GdfGQ s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG HYV JUMjMGJs
(3ai GdQO Ydi cJGH aVGFM GdHGWfjI ddEeGe GdZRGdi s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds